A busca pela cirurgia plástica estética: um sintoma da sociedade contemporânea? - Sousa, Manuela Silva Ferreira de (2007)
Youth and physical beauty are extremely important values in contemporary society. The way one thinks of his/her body is closely related to the cultural demands that influence the creation of one s body image, an important core component of personality. The study was conducted in Clinical Psychology and was based on Jungian approach, and its general purpose was to investigate whether women's search for aesthetic plastic surgery is determined by body image disorders and/or other mental disorders. The specific objectives of the research were to evaluate the self-perception, interpersonal perception and relationship satisfaction of these women, as well as specific psychological characteristics. The tools used in the study were a self administered questionnaire and the Rorschach test, permitting a quantitative and qualitative investigation of the signification processes connected to the body and the modification of the body due to aesthetic surgeries. Differently from the initial hypothesis, research findings tell us that the incidence of psychological disorders in respondents of this study is similar to that found in the compared population, of the same socioeconomic level and from the same city. A decrease in narcissistic defenses was noticed, as well as greater easiness in self-affirmation initiatives and a decreased isolation in relationships, permitting a positive attitude towards the world and significant interpersonal exchanges, although these women also have changes in terms of perception and thought, which interfere with the structuring of their body image. Therefore, aesthetic plastic surgeries are sought for different reasons or personality traits. Although the psychological meaning attributed to these surgeries denotes satisfaction, we noticed that the persona tends to be excessively dependent. Psychological help in the context of aesthetic surgeries is something desirable, because in addition to help preventing unsatisfactory or unnecessary procedures, it may render the persona more flexible and have a positive effect on the personal satisfaction of these women by enhancing their self-esteem and promoting their quality of life